Competitiveness of Various Segments of the Regional Consumer Market - Kuklina, Lyudmila Nikolaevna; Necheukhina, Nadezhda Semenovna; Mustafina, Olga Valeryevna (Economy of Regions, 2018)
Socio-economic development of a territory is particularly important in the context of the Russian society globalization, the acceleration of innovation, the emergence of new markets, increased competition for resources, as well as in the situation when consumers become the main factor determining the principles and methods of modern competition. Therefore, it is relevant to define the level of competitiveness of economic actor. The paper considers the criteria for the development of the consumer market’s retail segment. Furthermore, we have developed the model of competitiveness of local economic actors in the retail segment of the consumer market on the example of the Sverdlovsk region. As a result, we have formulated the conceptual framework for competitiveness of local economic actors in consumer market’s retail segment. Retail trade has socio-economic significance. Thus, there is a need to develop a consolidated framework for the competitiveness of economic actors in consumer market’s retail segment. Theoretical and practical experience of national and foreign researchers in this field has allowed us to suggest our position on the investigated problem. It is based on four components. The first one is theoretical foundations of the basic concept of competitiveness. The second component is the system of accounting and analysis. Thirdly, there are the system and methods of financial analysis. And the last component is the shareholder value model (EVA, VBM, DCF). The authors’ conceptual framework is based on the theoretical and methodological foundations of modern innovative tools for the financial management of competitiveness. The results of the research can become a basis for the development of new conceptual framework for the activities of local economic actors in the retail segment of the consumer market. It will ensure their effective strategic development.